A Study on Technology Integration Practices in Arts Instructors: Exploring the Mediating role of Value and Ability Beliefs - Tai, Ge; Nasir, Nadia Binti Mohd (South Asian Journal of Social Sciences and Humanities, 2024)
Teachers are the crux of every developing mind of newly blooming pupils in the education institutes and it is a universal factor in the learning process of every nature or aspect of study. Nowadays, the use of innovative technologies has become an essential practice in learning and teaching systems of every subject including art studies which indicates the constant incorporation of technology in instructional communication and reflects an advancement in the teaching process. Quantitative research design was implemented to assess the cause-and-effect relationship among variables. Primary data was collected through the survey strategy and a close-ended questions comprised questionnaire was designed. The researcher disbursed 350 questionnaires and finalized 331 questionnaires for the data analysis. The study encountered significant results for all synthesized associations except for the mediating role of ability beliefs. The present result hold numerous theoretical and practical implications. This study extends the growing body of literature regarding technology integration practices through the professional development, ICT knowledge and technical assistance. However, the study also provides practical implications as beneficial insights can be provided through which professional development can be fostered through technology integration practices. Research limitations and future indications have also been explained to increase the generalizability of this research.